Matteo Ricci, impulsor de la interculturalidad. Reflexiones desde la filosofía jurídico-política = Matteo Ricci, Driven Force for Interculturality. Reflections from the Legal and Political Philosophy - Carabante Muntada, José María (Isidorianum, 2025)
This article has the object of exposing the spiritual, cultural and socio-political implications of the mission of the Jesuits in China driven by Matteo Ricci. In addition to situating the specific context of the evangelization project, this paper describes the intellectual dimension of Ricci and the strategy of cultural accomodation ideated by Alessandro Valignano. Finally, Ricci proposes himself as an inspiring model to facilitate the crussing of cultures and religions, in that he is conscious of the universality of the faith and of the possibility that it is embodied in different cultural respectful with the doctrinal tradition of the Church.